Exploring Immune Development in Infants With Moderate to Severe Atopic Dermatitis - Hulshof, Lies; Overbeek, Saskia A.; Wyllie, Anne L.; Chu, Mei Ling J. N.; Bogaert, Debby; de Jager, Wilco; Knippels, Leon M. J.; Sanders, Elisabeth A. M.; van Aalderen, Wim M. C.; Garssen, Johan; van’t Land, Belinda; Sprikkelman, Aline B.; et al. (Frontiers in Immunology, 2018)
Background Atopic Dermatitis (AD) is the most common chronic inflammatory skin disease in infancy with a complex pathology. In adults, the clinical severity of AD has been associated with increases in Th2, Th22 and Th17 serum markers, including high levels of CCL17 and CCL22 chemokines. Objective To explore the possible association between serum chemokine levels and AD-severity in infants with moderate-to-severe AD and elevated IgE. Material and Methods Serum samples (n = 41) obtained from a randomised, double-blind, clinical dietary intervention study were used to study biomarkers in infants with AD. Baseline- and post-intervention samples (4 months) were used, six chemokines and nine ratios thereof were analysed using Luminex and correlated to AD severity. In the initial study the infants were randomised to receive extensively-hydrolysed whey-based formula without (control) or with scGOS/lcFOS (9:1) and Bifidobacterium breve M-16V (active). Results 31 Infants up to 11 months of age, with an objective-SCORAD score (oSCORAD) > 20 and elevated total-IgE and/or specific-IgE levels were included. In time the median oSCORAD decreased in both groups by -8 (control, p < 0.05; active, p < 0.01). Irrespective of dietary intervention, several changes in Th2 chemokines (CCL17 and CCL22), inflammatory chemokine (CCL20) and the Th1-chemokine, CXCL9, were detected over time. Overall CCL17 correlated to oSCORAD (r = 0.446, p < 0.01). After 4 months of dietary intervention, CXCL9 was higher (p < 0.01) in the active group compared to control (active, 2.33 (1.99-2.89); controls, 1.95 (1.77-2.43) log10 median (range)). In addition, a reduction in Th2/Th1-chemokine ratios for CCL17/CXCL9, CCL22/CXCL9, CCL20/CXCL10 and CCL20/CXCL11 was detected associated with the active intervention. Conclusion While this study is small and exploratory in nature, these data contribute to immune biomarker profiling and understanding of AD in infants.